Healthy Eating for Successful Living in Older Adults™ community education program—evaluation of lifestyle behaviors: A randomized controlled trial - Barnett, Junaidah B.; Zeng, Wu (Frontiers in Aging, 2022)
Objective: Older adults face many chronic health issues including heart disease and osteoporosis, which are preventable through changes in lifestyle behaviors. The Healthy Eating for Successful Living in Older Adults™ (HESL) is a six-week community education program designed specifically for persons aged ≥ 60 years, to promote behavioral changes towards a healthy lifestyle. Our objective is to evaluate the HESL. This is the first official evaluation of the HESL since its initiation in 2005. Study Design: A cluster randomized controlled trial. Method: Program implementation and evaluation took place between July 2018 and January 2020. Twenty-nine sites, with 292 participants aged ≥ 60 from across 5 states (mostly from Massachusetts), were randomized into the intervention group (IG) (16 sites; n=150 participants) and control group (CG) (13 sites; n=142 participants). The HESL workshops followed a scripted curriculum including information from the USDA’s MyPlateTM, and the USDA 2015-2020 dietary guidelines. Intervention elements included goal-setting, self-assessment, group support and problem-solving through brainstorming. The CG received no intervention. Outcome measures were collected in both groups at baseline, 2 weeks post-intervention (week 8), and 6 months post-intervention. These included self-reported lifestyle behaviors, a composite Healthy Behavior Index (HBI), BMI [Body Mass Index: weight(kg)/height(m2)] and WHR (Waist to Hip Circumferences ratio). Mixed-effects regression models were used to examine impact of the intervention. Results: The IG showed significantly improved responses to most healthy lifestyle behavior questions at week 8 compared to the CG. However, not all improved responses were sustained at month 6. Significant improvements detected at month 6 included responses to the question on making food choices that are healthy for the heart, using MyPlateTM tools for food choices, reading nutrition labels when shopping/planning meals as well as confidence in managing own health (p<0.001 in most cases). HBI was significantly improved at week 8 and month 6 (p<0.001). WHR decreased significantly (p<0.05) at month 6. Conclusion: Positive changes in lifestyle behaviors and WHR were observed in older adults due to the HESL intervention. This study is registered in clinicaltrial.gov with Identifier: NCT04991844; https://clinicaltrials.gov/ct2/show/NCT04991844 (334 words)